Performance Evaluation of Fuzzy Logic Based AODV and OLSR in MANET (International Journal of Communication Systems and Network Technologies, 2016)
Mobile Ad-hoc network (MANET) is a type of wireless network in which different wireless nodes connected in random manner. In this paper performances of AODV and OLSR have been analyzed using fuzzy logic controller. Fuzzy controller decided the value of Hello interval using two input parameters speed and battery power which is used in AODV and OLSR protocol. The performance of fuzzy based AODV and OLSR compared with conventional AODV & OLSR in terms of Average jitter, Average Throughput and End to End delay.
Keywords: MANET; AODV; Fuzzy Logic Controller; Hello Interval (HI); Fuzzy Based AODV (FBAODV); OLSR; Fuzzy Based OLSR (FBOLSR); QualNet 6.1